Accumulated environmental risk in young refugees – A prospective evaluation. (May 2020) - Begemann, Martin; Seidel, Jan; Poustka, Luise; Ehrenreich, Hannelore
Abstract: Background: Recently, we reported a strong, disease-independent relationship between accumulated preadult environmental risks and violent aggression later in life. Risk factors were interchangeable, and migration was among the explored risks. Alarmed by these data, we assessed collected risk load in young 'healthy' refugees as a specific subgroup of current migration streams and evaluated first signals of behavioral abnormalities. Methods: In 9 German refugee centers, n  = 133 young refugees, not previously in contact with the health system, were recruited, many of them unaccompanied minors. Risk factors experienced apart from migration/refuge were carefully assessed: Traumatic experiences before/during/after flight (including war, genocide, human trafficking, torture, murder, slavery, terrorist attacks), urbanicity, physical and sexual abuse, problematic alcohol and cannabis use (lifetime). Evaluation comprised physical exam and psychopathology screening. Findings: Refugees arrived in Germany via Eastern Mediterranean/Balkan route (34.6%), from Africa via Central Mediterranean route (39.1%), by plane (17.3%) or other routes, such as Western Mediterranean or Atlantic (9.0%). Flight reasons were war/expulsion (25.6%), persecution/threats to life (51.9%), economical/others (22.5%). On top of migration/refuge, 42.8% of subjects had ≥3 risk factors; only 4.5% of refugees had no additional risks. Global level of functioning and severity of psychopathology were strongly associated with number of accumulated risks (Jonckheere–Terpstra trend-test: p  = 7.61 × 10 −7 and p  = 3.62 × 10 −7, respectively). Interpretation: Young refugees, arriving in hosting countries with alarming 'risk burden', should be considered as highly vulnerable towards development of global functional deficits, behavioral abnormalities, and neuropsychiatric disorders. Rapid proactive integration or sustainable support of those who will return to rebuild their countries are mandatory. Funding: The Max Planck Society supported this work.